Towards the Use of Natural Compounds for Crop Protection and Food Safety (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In consideration of the ever-increasing global population, the demand for food—and on food-production—is massive. It is critical that we are able to meet this demand and mitigate the risks and factors that challenge our ability to do so, including pestilence to food crops and biological threats to food safety, before food reaches the consumer. As such, the advancement of measures to both protect crops and facilitate the surety of safe food products to end-users is a research area of great interest and growing development. This book details exciting new research into the use of natural compounds for the protection of crops and food products. From essential oils and their potential uses as naturally derived antimicrobial agents to the use of carbon dioxide as a pesticide and the use of biofertilisers, the articles herein describe and review cutting edge research in this area to help facilitate a more sustainable future.